Lexical access of bilinguals and multilinguals - Pâmela Freitas Pereira Toassi; Mailce Borges Mota (Acta Scientiarum: Language and Culture, 2015)
This paper presents studies on the lexical access of bilinguals with the aim of extending the assumptions of the bilingual lexicon to the study with multilinguals. For that, studies that investigated the Revised Hierarchical Model (RHM), the Bilingual Interactive Activation (BIA+) model and the models of speech production, on the serial and interactive views, are presented. Two models specifically designed for multilinguals are also presented in this paper: the Multilingual Processing Model and the Dynamic Model of Multilingualism. Based on this review of literature, research questions are raised to the investigation of the models presented with multilinguals.